2007
DOI: 10.1175/waf983.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Pacific Decadal Oscillation on Winter Precipitation and Drought during Years of Neutral ENSO in the Western United States

Abstract: The influence of the Pacific decadal oscillation (PDO) on important hydroclimatic variables during years of neutral ENSO for 84 climate divisions in the western United States is analyzed from 1925 to 1998. When the 34 neutral ENSO years are split by cold (12 yr) and warm (22 yr) PDOs, the resulting winter precipitation patterns are spatially similar to those that occur during years of La Niña-cold PDO and, to a lesser extent, years of El Niño-warm PDO, respectively, although the characteristic ENSO dipole is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 28 publications
2
66
0
Order By: Relevance
“…On time scales longer than ENSO, Pacific SST variability is dominated by the Pacific decadal oscillation (PDO), or Pacific decadal variability (PDV), which has a strong expression in the North Pacific Ocean (Mantua et al 1997;Zhang et al 1997). Much work has been done, mostly of an observational nature, suggesting that NA hydroclimate can be influenced by the PDO (e.g., Gershunov and Barnett 1998;Goodrich 2007;McCabe et al 2004McCabe et al , 2008. For example, differences in a variety of hydroclimatic variables can be seen in western NA between positive and negative phases of the PDO, even when only neutral ENSO years are considered (e.g., Goodrich 2007).…”
Section: F Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…On time scales longer than ENSO, Pacific SST variability is dominated by the Pacific decadal oscillation (PDO), or Pacific decadal variability (PDV), which has a strong expression in the North Pacific Ocean (Mantua et al 1997;Zhang et al 1997). Much work has been done, mostly of an observational nature, suggesting that NA hydroclimate can be influenced by the PDO (e.g., Gershunov and Barnett 1998;Goodrich 2007;McCabe et al 2004McCabe et al , 2008. For example, differences in a variety of hydroclimatic variables can be seen in western NA between positive and negative phases of the PDO, even when only neutral ENSO years are considered (e.g., Goodrich 2007).…”
Section: F Modelingmentioning
confidence: 99%
“…Much work has been done, mostly of an observational nature, suggesting that NA hydroclimate can be influenced by the PDO (e.g., Gershunov and Barnett 1998;Goodrich 2007;McCabe et al 2004McCabe et al , 2008. For example, differences in a variety of hydroclimatic variables can be seen in western NA between positive and negative phases of the PDO, even when only neutral ENSO years are considered (e.g., Goodrich 2007). And for various combinations of PDO and ENSO phases, drought and pluvial anomalies can be either amplified or diminished (e.g., Kurtzman and Scanlon 2007).…”
Section: F Modelingmentioning
confidence: 99%
“…Conversely, during the negative (cool phase) of the PDO, the Aleutian low is weaker and extratropical storms track farther north. When coupled with a La Niñ a phase, precipitation is enhanced in the U. S. Northwest and British Columbia, while in the southwestern United States, precipitation is decreased (Gershunov and Barnett 1998;Goodrich 2007).…”
Section: ) Enso Indicesmentioning
confidence: 99%
“…Two of the multi-year La Niñas (1955 to 1957 and 1999 to 2001) occurred during the warm phase of the AMO, which, when coinciding with the cold PDO, is also associated with drought in the western USA (McCabe et al 2004). Goodrich (2004Goodrich ( , 2007 recently found that neutral ENSO/cold PDO years are as dry as La Niña/cold PDO years. Unlike the other 2 multi-year La Niñas, the 1974 to 1976 multiyear La Niña occurred during the cold phase of the AMO.…”
Section: Comparison Of Causal Mechanismsmentioning
confidence: 99%
“…The PDO, which influences precipitation patterns in a manner similar to El Niño/ Southern Oscillation (ENSO), is positively correlated with winter precipitation in the southwestern USA. In fact, it is well established that the relationship between winter precipitation in the western USA and ENSO has varied in the past several decades, primarily due to changes in PDO phase (Gershunov & Barnett 1998, McCabe & Dettinger 1999, Gutzler et al 2002, Goodrich 2007. Barlow et al (2001) found that summertime precipitation, drought, and streamflow were positively correlated with both ENSO and PDO over the western United States such that drought conditions were most likely to occur during the cold phase of the PDO.…”
Section: Introductionmentioning
confidence: 99%